Influence of non-nutritive sucking habits on anterior open bite - Ana de Lourdes Sá de Lira; Alice Rodrigues Santos (Universidade Estadual de Campinas, 2020)
Aim: To evaluate the clinical behavior of sucking habits in children between 2 to 6 years old in a private (A1) and a public school (A2) in the state of Piauí. Methods: It was cross-sectional and quantitative study in 340 participants, 169 in A1 and 171 in A2. The researchers asked the children evaluated to keep their teeth occluded while analyzing whether there was no contact between the anterior teeth and no lip sealing, characterizing the anterior openbite for G1 or if there was contact between the incisors, with lip sealing, characterizing the control group (G2). Results: There was no statistically significant difference between groups regarding bottle feeding at main meals (χ2 = 3.03; p = 0.08). However, regarding the use of a pacifier, there was a statistically significant association (χ2 = 17.99; p <0.01) between pacifier use and the presence of anterior openbite. Such association was also observed between digital sucking habit and malocclusion (χ2 = 8.99; p = 0.01). Only the parents of the children with anterior openbite noticed the disharmony in the occlusion. It can be deduced that there was an awareness of parents /guardians about the disharmony generated by non-nutritive sucking habits. Conclusion: Nonnutritive sucking habits influenced the appearance of the anterior open bite in children with deciduous dentition. Nonnutritive sucking habits, such as digital sucking and pacifiers, are significantly associated with the presence of anterior open bite. Breastfeeding is important in preventing this malocclusion.